Prevalence of Leptospira spp. in Urban Rodents from a Groceries Trade Center of Medellín, Colombia (2009)
ABSTRACT: Leptospirosis is a widely distributed zoonosis, and rats are its most common source of infection. Our goal was to determine the frequency for Leptospira infection in rodents in a farmers market in the city of Medellin. We performed a descriptive transversal study sampling 254 rodents. Rodents were bled and killed, and kidneys samples were taken. Supernatants of macerated kidneys were cultured on Fletcher medium. Microagglutination tests (MATs) with 11 serovars were also carried out in rat serum, and a polymerase chain reaction (PCR) specific for pathogenic species was used to test each bacterial culture. All animals were identified as Rattus norvegicus ; 25% and 20% were positive by MAT and culture, respectively. PCR tests of 12 isolates were positive for pathogenic serovars, and 4 of them were confirmed as L. interrogans by sequencing. These data show the role of this natural carrier and shedder of pathogenic leptospires in the epidemiology of urban leptospirosis in Colombia.